Statistics with Confidence : Confidence Intervals and Statistical Guidelines. - Altman, Douglas (Wiley, 2013)
This highly popular introduction to confidence intervals has been thoroughly updated and expanded. It includes methods for using confidence intervals, with illustrative worked examples and extensive guidelines and checklists to help the novice.